Training on Preparation of Islamic Integrated HOTS-Based Questions and Their Application in Online Learning in Elementary Schools - Susilawati, Samsul; Yaqin, Muhamad Zubad Nurul; Wahidmurni, Wahidmurni; Ulfa, Fazat Arifatul; Krismoneta, Krismoneta (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
. The training for preparing Higher Order Thinking Skills (HOTS) Questions was motivated by the problems faced by Elementary Schools teachers in Malang Regency, in making learning evaluation questions given in assessing student learning outcomes so far, they are still at the Lower Order Thinking Skills level (LOTS). This is due to the lack of knowledge and understanding of teachers about the concept of HOTS and the lack of ability and skills of teachers in preparing HOTS-based questions. The training for preparing Higher Order Thinking Skills (HOTS) Questions was held at MI Hayatul Islam, Malang Regency, the training participants were Elementary Schools teachers in Malang Regency. This community service activity for the Masters of Education Master’s Program in Elementary Schools Postgraduate Islamic University Maulana Malik Ibrahim Malang Islamic University is carried out by providing training and assistance in preparing questions based on guidelines for writing HOTS questions, especially for grade IV and V teachers. Through lecture, question and answer, discussion, and In practice, this training turned out to be able to open up insight into the knowledge, understanding, and skills of teachers on how to compose questions and improve teachers' abilities and skills in making questions at the level of higher-order thinking skills so that they can be used to measure the development of students' thinking and reasoning abilities properly in accordance with the final results The expected learning is that students can think critically and creatively so that they can apply their knowledge and skills to identify and solve problems encountered in everyday life.